PEMISKINAN KORUPSI SEBAGAI SALAH SATU HUKUMAN ALTERNATIF DALAM TINDAK PIDANA KORUPSI - Ahmad Yani (SOL JUSTICIA, 2019)
This study aims to determine the concept of thought and the basis of corrupt criminal law is bad. In addition, it also aims to find out the implementation of the Criminal Code against bad corruption in Indonesia. The research method used in this study is normative legal research. This is research that focuses on positive legal norms which are legal codes with data sources derived from primary and secondary legal materials. Data analysis was carried out on primary and secondary legal materials and compared the two. Based on the results of the study, it was revealed that the bad corruptors as a legal idea can provide great lessons for actors and others. Bad corruptors can oppose acts of corruption that are greatly increasing. The concept of bad corruptors can be done by taking over assets that are the takeover of all goods as a result of acts of corruption and / or by paying compensation for losses due to corruption. In its implementation, corrupt corruption that is bad in Indonesia has not been carried out explicitly. Law enforcers in eradicating corruptors have not executed bad corruptors as a legal action.